A novel study of using oil refinery plants waste gases for thermal desalination and electric power generation: Energy, exergy & cost evaluations. (1st June 2017) - Sharaf Eldean, Mohamed A.; Soliman, A.M.
Graphical abstract: Highlights: Waste gases from oil refinery plants are burned for thermal desalination and electric power generation. Heat from waste gases powered on ORC and gas turbine cycle. Hybrid MSF and MED is used in the performed work. Abstract: Thermal desalination plants need large amounts of fuel to desalinate large quantities of seawater. At the same time, burning non-beneficial gases in the oil refineries is considered a huge waste of energy instead of using it. In this paper, a novel study on the possibility of operating the thermal desalination plants by waste gases that emerged from oil refineries rather than burning these gases in the air is performed. Hybrid MSF-MED thermal desalination processes are utilized in this study to produce a total range of 100–40, 000 m 3 /day. Three scenarios are performed utilizing the waste gases with MSF-MED. The comparison brings out that using waste gases would save roughly 1136 $/h (UHC-unit hourly costs, $/h) while comparing against the conventional natural gas operation. Moreover; 5 m 3 /h of waste gases would produce an amount of 58–60 MW of electric power combined with a production of 100 m 3 /d of fresh water (gas turbine cycle scenario) and 4.5–5 MW combined with a production of 40, 000 m 3 /d in case of organic Rankine cycle operation. Based on energy and exergy balances, the 3rd scenario gives remarkable results.